(untitled) (Research, Society and Development, 2020)
Introduction: Systemic arterial hypertension represents a serious public health problem. The most appropriate approach in hypertensive crisis is the ambulatory and clinical evaluation, including detailed physical examination. Objective: To identify, in the literature, the activities developed by the nurse during the nursing consultation to the patient with hypertensive crisis who is accompanied in primary care. Methods: An integrative review study was conducted with data collection from May to June of 2020, in the data bases: LILACS and BDENF. The inclusion criterias were based on full articles about the topic available online, in Portuguese and English, from the last ten years. Of the total of 620 articles found after crossing the descriptors, only 17 were selected for analysis, according to the inclusion criteria. Results: In the basic health unit, care for patients with hypertensive peak includes risk stratification, in addition to the use of medication, the evaluation of signs and symptoms and referral to priority cases of more severe problems, as well as the execution of care that can favor a better approach to the patient with hypertensive crisis. Conclusion: It is up to the nursing team to take care of the control of arterial hypertension, thus, it is relevant to provide information about it to patients and their families in order to encourage self-care.